Implementasi Peraturan Daerah Berbasis Syariah Di Pantai Tanjung Bira - Aninda Aprilia; Idris Parakkasi; Sirajuddin (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2023)
Regional Regulation Number 3 of 2002 concerning Prohibition, Supervision, Control, Distribution and Sale of Alcoholic Drinks andRegional Regulation Number 5 of 2003 concerningMuslim Women and Muslim Women's Clothing are two examples of sharia law that have beenimplemented in Bulukumba Regency. To understandand assess the community's reaction to the formationof Sharia-Based Regional Regulations at Tanjung Bira Beach, Bulukumba Regency, this study seeks tounderstand the mechanisms and implementation ofpolicies as well as policy implementation. Suchstudies use a phenomenological approach and focus onhow individual participants perceive their experiences. based on an investigation into the spike in alcohol useamong Bulukumba residents and questions about theclothing worn by tourists. The regional governmentand its staff, especially Kesbangpolinmas and Satpol Pamong Praja, have attempted to interact and persuadeyoung people who use alcohol and traders who sellalcohol, especially regional drinks, by taking firmaction against violations of regional law, formingBuserda Teams (Regional Hunters and Sergeants), andcarrying out supervision and enforcement of alcohol in the field. They also gave strict warnings to employeeswho were not wearing Muslim clothing and were drunk. The community responded positively to theimplementation of this regional regulation which madeTanjung Bira Beach, Bulukumba Regency, experiencea decrease in crime rates.